Local Culture and Political Reproduction: Cultural Mechanisms of Electoral Dominance among Bugis Political Elites in Bone Regency - A. Burchanuddin; Arief Wicaksono; Sobirin (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
This study examines the role of social capital in the political reproduction of elites in Bone Regency, Indonesia, addressing a significant gap in the local politics literature, which has predominantly emphasized economic and political determinism. A qualitative approach with an in-depth case study design was employed. Data were collected through in-depth interviews, field observations, and document analysis involving political elites, traditional leaders, and grassroots voters. The findings reveal that the enduring electoral dominance of Bugis political elites is sustained not merely by financial resources but through the systematic operation of the Cultural Mechanisms of Electoral Dominance (CMED) model. Political elites strategically convert economic capital into long-term social capital by strengthening kinship networks (assiasangeng) and maintaining traditional patron-client relationships (punggawa-sawi). This sustained social investment generates a process of the euphemization of power, whereby material exchanges are transformed into morally legitimate social relationships grounded in Bugis cultural values, including siri', pesse, lempu', and getteng. These mechanisms produce symbolic violence and an electoral doxa, leading constituents to voluntarily reproduce dynastic political dominance because it is perceived as a natural, legitimate, and morally appropriate social order. The study contributes theoretically by reconceptualizing transactional clientelism as Relational-Moral Clientelism, thereby extending Bourdieu's theory of practice within the context of local electoral politics. It concludes that the reproduction of elite political power is deeply rooted in subtle forms of cultural hegemony. These findings suggest the need to redesign electoral oversight regulations by empowering the Election Supervisory Agency (Bawaslu) to monitor political philanthropy beyond official campaign periods, while also strengthening critical political education to enhance voters' democratic awareness. Future research should undertake comparative studies in non-feudal settings and explore the transformation of political habitus among younger generations.